2016
DOI: 10.1177/1534734616636271
|View full text |Cite
|
Sign up to set email alerts
|

Serratia marcescens Bullous Cellulitis in a Splenectomized Patient

Abstract: Serratia marcescens is a Gram-negative bacillus belonging to the Enterobacteriaceae family. Cutaneous infection with Serratia is rare, and usually occurs in immunocompromised individuals. Primary cutaneous infections are uncommon, but they are typically severe and are associated with significant morbidity and mortality. The pathogenetic factors leading to S. marcescens infection are not fully understood, but contributing virulence factors include proteases, secreted exotoxins, and the formation of biofilm. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Presentations include isolated plaques, 15 bullous cellulitis, 16 papillovesicular eruptions, 17 abscesses, 18,19 nodules, 20,21 granulomatous lesions, 22,23 and necrotizing cellulitis. 24 Cases have been reported in the extremities of patients with uncontrolled diabetes 25 and end-stage renal disease, 26 as well as those who have undergone splenectomy 27 and chemotherapy. 17 Infections associated with immunocompromised state frequently disseminate and lead to life-threatening sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Presentations include isolated plaques, 15 bullous cellulitis, 16 papillovesicular eruptions, 17 abscesses, 18,19 nodules, 20,21 granulomatous lesions, 22,23 and necrotizing cellulitis. 24 Cases have been reported in the extremities of patients with uncontrolled diabetes 25 and end-stage renal disease, 26 as well as those who have undergone splenectomy 27 and chemotherapy. 17 Infections associated with immunocompromised state frequently disseminate and lead to life-threatening sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Other forms of being immunocompromised in patients with S. marcescens cellulitis or NF included a history of splenectomy, chronic steroid use, and neutropenia from chemotherapy. 1,[5][6][7] In addition to an immunocompromised state, factors that are thought to predispose patients to the skin and soft tissue infections from S. marcescens include external trauma and compromised skin integrity such as chronic venous stasis. 4,5 This patient had chronic kidney disease, diabetes mellitus, and end-stage liver disease, all of which have been associated with high mortality in patients with cellulitis secondary to S. marcescens.…”
Section: Risk Factorsmentioning
confidence: 99%
“…A mice model has shown that cell-mediated immunity in the spleen helps clear Serratia marcescens and so splenectomized patients are at high risk of developing severe soft tissue infection. 5…”
Section: Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations